VARIASI KONSENTRASI PEKTIN KULIT DURIAN TERHADAP KARAKTERISTIK FISIK DAN MEKANIK EDIBLE FILM DARI PATI UBI JALAR UNGU - Lesmana, Indra; Ali, Akhyar; Johan, Vonny S (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aims to determine the best concentration of durian leather pectin and to repair physically and mechanically of edible film of purple sweet potato starch. The research was carried out experimentally by Completely Randomized Design with four treathments and four replications. It used different concentrations of durian leather pectin, which consist of 0, 10%, 20%, and 30%. The data obtained were analyzed statistically using Analysis of Variance and followed by Duncan’s New Multiple Range Test test at 5% level. The parameters observed are the film thickness, the steam transmission rapid, the film solubility, tensile strength, and elongation. Results of ANOVA showed that the variation of durian’s leather pectin which influenced all parameters test. The best treatment for this research was edible film from purple sweet potato starch with adding 30% durian leather pectin.  Edible film for this treatment has 0.1280 thickness value, 5.9112 grams/m2.hour steam transmission rapid, 89.9575% solubility, 8.680MPa tensile strength, and 23.5637% elongation.   Keyword: Edible film, starch, purple sweet potato, durian leather pectin